2017
DOI: 10.1111/jcmm.13197
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic effects of clove buds (Syzygium aromaticum L.) in the model of breast carcinoma

Abstract: It is supposed that plant functional foods, rich in phytochemicals, may potentially have preventive effects in carcinogenesis. In this study, the anticancer effects of cloves in the in vivo and in vitro mammary carcinoma model were assessed. Dried flower buds of cloves (CLOs) were used at two concentrations of 0.1% and 1% through diet during 13 weeks after the application of chemocarcinogen. After autopsy, histopathological and immunohistochemical analyses of rat mammary carcinomas were performed. Moreover, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 51 publications
9
76
1
Order By: Relevance
“…Hence, inhibition of cardiomyocyte apoptosis can ameliorate myocardial dysfunction after I/R injury and limit myocardial remodeling development [32]. Although previous studies have revealed that TIMP3 plays an important role in regulating apoptotic activity in certain cancers [33, 34], prior to present study, it is unclear whether TIMP3 is involved in myocardial apoptosis undergoing I/R injury. The present data demonstrated that upregulation of TIMP3 inhibited myocardial apoptosis, as evidenced by reduced TUNEL-positive cells.…”
Section: Discussionmentioning
confidence: 46%
“…Hence, inhibition of cardiomyocyte apoptosis can ameliorate myocardial dysfunction after I/R injury and limit myocardial remodeling development [32]. Although previous studies have revealed that TIMP3 plays an important role in regulating apoptotic activity in certain cancers [33, 34], prior to present study, it is unclear whether TIMP3 is involved in myocardial apoptosis undergoing I/R injury. The present data demonstrated that upregulation of TIMP3 inhibited myocardial apoptosis, as evidenced by reduced TUNEL-positive cells.…”
Section: Discussionmentioning
confidence: 46%
“…In our previous paper [12] we described anti-cancer activity of CBE extract in breast cancer model in vitro and in vivo. The results obtained pointed out to significant pro-apoptotic, antiproliferative and anti-angiogenic effects of CBE in mammary carcinoma model.…”
Section: Resultsmentioning
confidence: 99%
“…0.4% with no toxicity. Secondary metabolites identification in CBE extract was performed and characterised as was described in previous paper [12].…”
Section: Cell Cultures and Cbe Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44 and CD24 are characteristic of the cancer stem cell phenotype, and these molecules are closely associated with poor prognosis and chemotherapy resistance in cancer. [24][25][26][27] Recently, natural substances from plants have been documented as effective intervention agents in the down-regulation of CD44/CD24 expression in experimental breast carcinoma. 28 However, whether IBC can directly regulate CD44/CD24 expression to decrease paclitaxel resistance in ER+ breast cancer cells remains unclear.…”
mentioning
confidence: 99%